2014
DOI: 10.1037/h0099377
|View full text |Cite
|
Sign up to set email alerts
|

Expressive writing and posttraumatic growth: An Internet-based study.

Abstract: This explorative study examines the effects of an internet-based expressive writing intervention on posttraumatic growth. Participants were randomly assigned to either an expressive writing condition (n = 14) or a control writing condition (n = 10), with participants writing for 15 minutes on three separate occasions spaced 3 days apart. Measures of intrusive and avoidant trauma-related thoughts and posttraumatic growth were administered at baseline, 2 week and 8 week post-intervention follow-up. Results indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 61 publications
0
19
0
1
Order By: Relevance
“…[51] Expressive writing and reflection are similar, although reflection is focused on a "critical analysis" of the event, [54] whereas expressive writing concentrates more on a simpler recounting of the event. [55] The literature provides many examples of how participating in an expressive writing intervention may improve mental [41,50,52,56] and physical health. [28,39] A new perspective regarding the past event and ability to handle new stressful situations may occur because of the "cognitive change".…”
Section: Reflectionmentioning
confidence: 99%
“…[51] Expressive writing and reflection are similar, although reflection is focused on a "critical analysis" of the event, [54] whereas expressive writing concentrates more on a simpler recounting of the event. [55] The literature provides many examples of how participating in an expressive writing intervention may improve mental [41,50,52,56] and physical health. [28,39] A new perspective regarding the past event and ability to handle new stressful situations may occur because of the "cognitive change".…”
Section: Reflectionmentioning
confidence: 99%
“…Ayrýca bazý araþtýrmalar açýða vurmalarýn evde gerçekleþtirilmesinin saðlýðý daha fazla geliþtirebileceðine dikkat çekmektedir (26). Bu nedenle gelecek çalýþmalarda evde yürütülen ya da internet ortamýnda gerçekleþtirilen yazma seanslarýnýn (40,55,62) test edilmesinin önemli olacaðý söylenebilir.…”
Section: Gýrýþunclassified
“…First, this study involved active burn survivor bloggers, so the results cannot be generalised across the wider burn survivor population. A recent study by Stockton et al (2014) has found that trauma sufferers who expressively wrote about their experiences showed an increase in post-traumatic growth, compared to a control writing group who were asked not to make reference to feelings or opinions, or their traumatic experience. Therefore, the data from this population cannot be generalised to non-blogging burn survivors.…”
Section: Study Limitationsmentioning
confidence: 99%